A Brief Overview on Corona Virus Disease-2019 (COVID-19): Epidemiology and Severity - Disha Chouhan; Rajesh Mujariya (Current Innovations in Disease and Health Research Vol. 3, 2023)
This chapter describe the Epidemiology, Severity of COVID-19 and Practice Points from an Indian Perspective. With the introduction and spread of the 2019 novel corona virus (2019-nCoV) or the severe acute respiratory syndrome corona virus 2 (SARS-CoV-2), there is a new public health disaster that threatens the entire world. In December 2019, the virus spread from bats to humans via unidentified intermediary species in Wuhan, Hubei Province, China. The disease is transmitted by inhalation or contact with infected droplets and the incubation period ranges from 2 to 14 d. effective treatment forSARS-CoV-2 is lacking; however, two trials investigating the clinical efficacy of remdesivir are underway in China. Currently, effective infection control intervention is the only way to prevent the spread of SARS- CoV-2.